Strategi Pengembangan Ekonomi Kreatif Perdesaan Berbasis Potensi Lokal untuk Meningkatkan Pendapatan di Kawasan Pasar Terapung Lok Baintan - Majidah, Hikmah; Rahmini, Noor; Sopiana, Yunita (Ecoplan, 2025)
Poverty in rural areas is still one of the main challenges that hinders the improvement of people's welfare, especially in the Lok Baintan Floating Market area. Despite the abundant potential of local natural resources and culture, the lack of innovation and effective use of technology and marketing has led to limitations in developing the creative economy. Therefore, this research was conducted to formulate a creative economy development strategy based on local potential to increase community income in the region. This study used a descriptive qualitative approach. In particular, it explored case studies in three main villages: Lok Baintan Village, Sungai Tandipah Village, and Paku Alam Village. To achieve the objectives, data was obtained through in-depth interviews with village officials and business actors. In addition to that, field observations and documentation studies related to local economic policies and potential were also employed to enrich the data reliability. The data were then analyzed using the SWOT analysis to identify strengths, weaknesses, opportunities, and threats that affect the development of the creative economy in the Floating Market area. The results showed that despite potential advantages such as low start-up capital and abundant human resources, the main obstacles were related to the lack of innovation, marketing technology, and infrastructure support. Therefore, the proposed strategy includes increasing the capacity of business actors through innovation training, optimizing the use of digital media, and strengthening the role of Village-Owned Enterprises (BUMDes) in managing the creative economy. Thus, implementing this strategy is expected to increase community income and encourage sustainable creative economic growth in the Lok Baintan Floating Market area.